Anticoagulant Therapy in Patients with Non-valvular Atrial Fibrillation in Real Clinical Practice: in Appropriate Dose Reductions - V. A. Ionin; O. I. Bliznuk; E. I. Baranova; E. V. Shlyakhto (Столичная издательская компания, 2021)
Aim. To study the frequency of administration of direct oral anticoagulant (DOACs) in doses recommended and not recommended by the instructions of the drugs in non-valve atrial fibrillation (AF) patients.Material and methods. 10663 case histories of patients hospitalized for 5 years (2014-2018) were studied, 1307/10663 (12,3%) case histories of patients with AF were selected. In patients with AF, the risk of stroke and systemic embolism, the risk of bleeding, the anticoagulant therapy (ACT) recommended at the prehospital stage and its adequacy was evaluated.Results. 1 261/1 307 (96,5%) patients had a non-valve AF. The risk of stroke and systemic embolism was 4,7±1,5 (CHA2DS2-VASс), 97,5% of patients with non-valve AF (1229/1261) needed ACT. Only 665/1229 (54.1%) patients with AF received ACT at the time of hospitalization and 578/1229 (47,0%) of patients did not receive ACT. Before hospitalization 281/665 (42,3%) patients received vitamin K antagonist (warfarin). The international normalized ratio in the target range (2,0-3,0) was in 111/281 (39,5%) patients. 57,7% (384/665) outpatients with AF received NOAC: rivaroxaban - 180/384 (46,9%) patients, dabigatran etexilate - 110/384 (28,6%) patients, apixaban - 94/384 (24,5%) patients. Inappropriate reduced doses of DOAC were revealed in 68/384 (17,7%) patients: apixaban - 23,4%, dabigatran - 16,4% and rivaroxaban - 15,6% (p>0,05).Conclusion. In real clinical practice 42,3% AF patients used warfarin, only 39,5% of them had INR in target values. DOAC in inappropriate reduced doses used 17,7% patients.